Dermatology life quality index in patients of acne vulgaris presenting to a tertiary care hospital: an observational study - Kundale, Darshana R.; Gosavi, Anil P.; Chavan, Ravindranath B.; Bhatt, Neelamkumari (International Journal of Research in Dermatology, 2021)
Background: Acne vulgaris is a common, chronic disorder resulting from the inflammation of pilosebaceous unit, present with clinically various forms. It is usually prevalent in adolescent may persist in adulthood. This study was conducted to evaluate the quality of life (QoL) in patients suffering from acne vulgaris. Methods: Hospital based cross sectional study was conducted in 60 patients. Dermatology life quality index (DLQI) questionnaire was used to observe the effect of acne among patients. Results: Total numbers of patients enrolled were 60 (43 females,17 males). The mean age was 24.85±5.63 years. Maximum patients were of the age group 26-30 years (22 patients; 36%) and least were of 31-36 age group. Out of 60 patients, 29 patients had grade II acne followed by 20 with grade I acne, grade III acne was present in 11 patients. Most of the patients 31 (52%) were having “moderate impact” on quality of life followed by 23 (38%) with “small impact” on QOL. There was a significant positive correlation between grade of acne and DLQI (Pearson correlation=0.753, p=0.00). Conclusions: Our study showed significant impairment of QoL in acne patients. DLQI increases with increase in severity of acne. Treatment of acne should not be guided only by the clinical grade of acne, but take into consideration the psychosocial impact the condition has on the patient. Adequate counselling along with early treatment of acne vulgaris is essential in order to reduce the disease related psychosocial sequelae and increase treatment efficacy.